2014
DOI: 10.4103/0973-029x.140909
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma of submandibular salivary gland: A rare case report

Abstract: Malignant tumors of submandibular salivary gland are rare in occurrence. Squamous cell carcinoma of salivary glands accounts for about 0.9-4.7% of all salivary gland tumors with a predilection to occur in parotid gland due to perinodal involvement. Primary squamous cell carcinoma of submandibular salivary gland accounts to about 2% of the tumors and hence it is being represented for its rarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…While all metastatic SCCs involved the parotid gland, primary SCCs affected both parotid and submandibular glands. The parotid gland is the most commonly involved major gland in primary SCC [1,3,14], although many isolated cases of submandibular gland origin have been reported [4,5,16,22,23]. The location of primary SCC as well as the age and sex of the patients were similar to those reported for salivary duct carcinomas.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…While all metastatic SCCs involved the parotid gland, primary SCCs affected both parotid and submandibular glands. The parotid gland is the most commonly involved major gland in primary SCC [1,3,14], although many isolated cases of submandibular gland origin have been reported [4,5,16,22,23]. The location of primary SCC as well as the age and sex of the patients were similar to those reported for salivary duct carcinomas.…”
Section: Discussionsupporting
confidence: 61%
“…Primary squamous cell carcinoma (SCC) of the salivary gland is a rare disease, accounting for 1.6% (0.3%-6.9%) of salivary gland neoplasms [1][2][3][4][5]. The salivary gland is histologically composed of secretory, ductal, and myoepithelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The patient underwent wide excision and neck dissection for metastatic lymph nodes in neck. Manvikar et al, also reported a case similar to the present one where a 70-year-old female presented with rapidly growing submandibular swelling and was diagnosed as squamous cell carcinoma [7]. According to Rao et al, in a case report of submandibular squamous cell malignancy, the patient expired within 4 months of diagnosis due to pulmonary metastasis, highlighting the aggressive behaviour of these tumours [8].…”
Section: Discussionmentioning
confidence: 77%
“…They are unusual in patients younger than 20 years, although several cases have been described. Males are more frequently affected than females [3,8]. The major risk factors include smoking, alcohol consumption and Betel quid chewing [1].…”
Section: Discussionmentioning
confidence: 99%